Systematic Literature Review (Slr) : Work Productivity Loss Among Women With Menopausal Symptoms - Tri Niswati Utami; Ira Riswana; Nabila Audria; Zelsy Casandra Nevanayu; Elza Rachma Fadilah; Monica Amelia; Fadiyah Nurhasanah S; Syaidil Amri (Lembaga Pengembangan Kinerja Dosen, 2023)
Women make up almost half of the workforce in developed countries; the majority may experience various menopausal symptoms into their decade of employment. This SLR aims to investigate the impact of menopausal symptoms in a work context. This method was systematically searched to identify studies that assessed reduced productivity and menopausal symptoms. Searches were conducted according to PRISMA guidelines. Electronic search is complemented by targeted search; publications were screened by two independent reviewers. Results From 3,850 identified records, 5 studies were included. reported in women with vasomotor menopausal symptoms (VMS) compared with other women. Conclusion Menopausal symptoms weigh heavily on individual careers and society. The impact of menopausal symptoms is not uniform and tends to be underestimated given women work outside of paid jobs. Holistic impact assessment included. consideration of gender gaps and equality is needed to improve interventions for working menopausal women.